Stable and unstable forms of human fibroblast interferon. - Edy, V G (1977)
There is a minor fraction of human fibroblast interferon that resembles human leukocyte interferon in being renaturable after treatment with guanidine hydrochloride. However, antigenically and in its low activity on heterologous cells, it resembles the bulk of human fibroblast interferon. Since the production of this stable interferon fraction is not greatly inhibited by glucosamine at concentrations that significantly reduce total interferon production, it is suggested that it differs from the bulk of human fibroblast interferon in the extent or nature of glycosylation.